Commissioning for change: A new model for commissioning adult social care in England. (August 2019) - Hudson, Bob
Adult social care policy and provision in England has changed from a state to a market model over the past 50 years, yet its future is far from settled. Dissatisfaction with funding, the range and quality of provision, and with workforce conditions is widespread. Some major providers have collapsed or withdrawn from the market. For some the solution is to strengthen the market model, others hark after a return to state controlled provision. This article outlines a further option, a radical new model for commissioning and delivery that challenges the dominant balance of power. It identifies some of the problems associated with the current position but questions the feasibility of a simple 'renationalisation' of provision. The key to change is identified as a new approach to commissioning consisting of four dimensions: commissioning small and local; commissioning holistically; commissioning personally; and commissioning ethically. All of these involve significant challenge to the way decisions are currently taken.